EFEKTIVITAS PEMBERIAN EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP PRODUKSI ASI DAN KENAIKAN BERAT BADAN BAYI: THE EFFECTIVENESS OF MORINGA OLEIFERA LEAF EXTRACT ON BREAST MILK PRODUCTION AND BABY WEIGHT GAINS (Politeknik Kesehatan Kemenkes Bandung, 2022)
The failure of exclusive breastfeeding is caused by internal and external factors. Internal factors, one of which can be caused by the mother's physical condition and must fulfill nutrition, because at the time of delivery the mother bleeds and 50% of the baby's iron needs come from the mother. The purpose of this Evidence Based Case Report is to determine the effect of giving Moringa leaf extract on breast milk production and increased baby weight. The Evidance Based Case Report method used is by using evidence search through the Google Scholar, Portal Garuda, Siencedirect, Pubmeed and Chocrane Library databases. Where the articles / journals used are research articles from 2016-2021. The inclusion criteria used are full text articles, English or Indonesian, there are three journals that can be used in accordance with the objectives of the Evidence Based Case Report. The results of this Evidence Based Case Report, were evaluated on day 7 with the results of expressing 38 ml of breast milk and increasing the baby's weight by 100 grams. There is a significant effect of giving Moringa leaf extract on breast milk production and increasing baby's weight Keywords: Moringa leaf (Moringa Oliefera), breast milk production, baby's weight